Internal Protective Factors That Affect The Resilience Of Hemodialysis Patients: Scoping Review - Swastika Sekar Utami; Meira Erawati; Nur Setiawati Dewi (Jurnal Berita Ilmu Keperawatan, 2023)
Internal protective factors are factors that come from the individual to support a resilient condition due to the hemodialysis process. The hemodialysis process causes many changes to patients with chronic kidney failure, such as changes in eating, drinking and activity patterns. These factors are the main factor that arises from oneself so it will bring motivation in the process of life going forward. This research is a scoping review which aims to determine the internal protective factors which can affect the resilience of hemodialysis patients. Articles are filtered from science direct, Scopus, PubMed, and Proquest. The keywords used are “factors” AND “Resilience” AND “hemodialysis patient”. The articles used are articles published from 2019-2023. The articles included are full articles, in English, using qualitative, quantitative and mixed methods. The analysis used in this review is the analytical method of Arksey and O'Malley in 6 stages. There were 7 articles analyzed at the end of the search. The protective internal factors obtained are the ability to regulate emotions, optimism, self-esteem, strength and self-confidence as well as spiritual well being. These factors have a positive influence in realizing the resilient condition of hemodialysis patients. This research can be continued with the application of nursing interventions to improve the internal ability of hemodialysis patients to achieve a resilient condition.